Psychosocial Barriers and Enablers for Prostate Cancer Patients in Starting a Relationship. Issue 8 (16th November 2020) - Mathew, Sandra; Rapsey, Charlene M.; Wibowo, Erik
Abstract: Single prostate cancer (PCa) patients may face difficulties in starting a new relationship for various reasons. Here, we studied barriers and enablers to starting a relationship for PCa patients and characteristics of patients who were and were not in a relationship. PCa organizations distributed for us a 20-minute online survey, consisting of validated questionnaires (on treatment side effects, loneliness, social provision, and shyness) and questions on factors identified by patients as barriers and enablers to forming a new relationship. Participants were either single [ n = 20] or had started a new relationship post-diagnosis [non-single, n = 15]. Three factors—confidence, sexual function, finding the right person—were perceived of as factors that can affect starting a relationship. Fourteen of twenty single patients were confident that they could find a partner and sixteen were comfortable in disclosing their cancer diagnosis to a potential partner. Non-single patients met their partners through various ways, including online dating and social events. They all revealed their cancer status prior to starting the relationship, and most partners reacted well to this disclosure. Single patients were lacking emotional support, more shy, and lonelier than non-single patients. Clinicians need to consider biopsychosocial factors when advising single patients who wish to start a new relationship.